2006
DOI: 10.1080/02646830500475237
|View full text |Cite
|
Sign up to set email alerts
|

Infant temperament: an evaluation of children with Down Syndrome

Abstract: The current study investigated differences in the development of temperament for normally developing infants and infants with Down Syndrome (DS). DS has been described as the most prevalent cause for mental retardation, and its effects on the central nervous system may also influence the development of temperament. Parents of 3 to 12 month-old normally developing infants and infants with DS completed the Infant Behavior Questionnaire-Revised (IBQ-R). Results indicated that parents of infants with DS described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Although comparable in size to other published research on children with DS ( n = 17, as in Gartstein et al . ; n = 15, as in Gunn et al . ), subsequent research should include a greater number of participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although comparable in size to other published research on children with DS ( n = 17, as in Gartstein et al . ; n = 15, as in Gunn et al . ), subsequent research should include a greater number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to their TD counterparts, infants with DS also experience less distress when placed in limiting situations, they obtain more pleasure from low‐intensity stimuli (those that are relatively less intense, complex and novel than others), they attend to stimuli for greater durations of time, they are easier to comfort and they are cuddlier (Gartstein et al . ). Other studies indicate that infants with DS are more commonly identified as having difficult temperament profiles relative to controls matched on presumed DA, although this difference tends to diminish over time.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Children with Down syndrome display lower levels of negative emotionality than typically developing children (Nygaard et al . 2002; Gartstein et al . 2006) and as having Down syndrome appears to protect against development of SIB (Cooper et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas the ADHD group had higher novelty-seeking scores, the ASD group had lower noveltyseeking, reward dependence and attachment scores (on the Temperament and Character Inventory) all associated with extraversion. Similarly, while children with developmental delay such as Down syndrome have lower scores on scales associated with effortful control (Gartstein et al 2006;Marcovitch et al 1986;Pueschel and Myers 1994) and difficulty regulating frustration (Jahromi et al 2008), they show either no difference in extraversion (Gartstein et al 2006;Landry 2000) or higher levels of approach than typical controls and children with ASD (Landry 2000;Marcovitch et al 1986;Pueschel and Myers 1994). In Williams syndrome, a developmental disorder associated with low IQ, high levels of anxiety, and some social impairments (see Tager-Flusberg and Plesa-Skwerer 2006, for a review), higher scores on negative affectivity have been reported relative to a clinical control group, but scores on various scales associated with extraversion are also higher.…”
Section: Temperament Profiles Associated With Asdmentioning
confidence: 99%